Gestión administrativa y financiera del parque acuático Josefina Barba .de la parroquia Balsapamba. Canton San Miguel, provincia Bolivar, periodo 2014-2016 - Bonilla García, Jannyna Alexandra (2016)
The present investigation was carried out by means of a field study directed to the Autonomous Government Decentralized of the Province Bolivar, discovering as a problem deficient actions in the Administrative and Financial Management of the Josefina Barba Aquatic Park, that is to say the managers do not have an efficient management in development Of the activities of this tourist center which does not contribute to the objectives of the GADPB. For this reason the scientific question arises how the administrative does and financial management influence on the sustainability of the "Josefina Barba" water park, Balsapamba Parish Canton San Miguel, Provincial Bolívar? , With the purpose of verifying it through scientific questions, describing the key points and critics that affect the administrative and financial management and within these we have: firstly, the administrative process that includes the four fundamental elements that Are planning, organization, direction and control, this affects the budget part of the GADPB, we also have the economic crisis that Ecuador is going through today, which undoubtedly affects these aquatic entertainment centers because of the Income and expenses demanded in the family sustainability. This leads to put greater emphasis and concern on administrative and financial management because they are not meeting the collection goals established in this administration affecting the budget of the GADPB. And therefore in its distribution in works that benefit the good life of the Bolivarian. To reach the proposed objective, a background study was carried out using research methods and techniques such as surveys, interviews; Reaching the conclusion that the authorities do not comply with the majority with the appropriate administrator process that guarantee an efficient and effective management. Finally, it can be argued that if the authorities and administrators make the updating and the appropriate use of administrative and financial management, they will be able to obtain greater revenues, achieving sustainability in the Josefina Barba Water Park.